Pengembangan Citra Merek sebagai Identitas Merek “Arak Besan” dalam Menghadapi Kompetitor - Nyoman Sri Subawa; Ni Wayan Widhiasthini; Ni Putu Intan Permatasari; Ni Nyoman Sri Wisudawati (Penerbit Goodwood, 2022)
Purpose: provide training and understanding of the importance of brands in product development and marketing. Method: Training and counseling for